Association between forefoot bone length and performance in male endurance runners - Ueno, H.; Suga, T.; Takao, K.; Tanaka, T.; Misaki, J.; Miyake, Y.; Nagano, A.; Isaka, T. (International Journal of Sports Medicine, 2018)
Recently, we reported that the forefoot bones were longer in sprinters than in non-sprinters, and that longer forefoot bones correlated with higher sprint performance in sprinters. To further understand the superiority of long forefoot bones in athletic performance, we examined whether forefoot bone length was associated with running performance in endurance runners. The length of the forefoot bones of the big and second toes were measured using magnetic resonance imaging in 45 male well-trained endurance runners and 45 male untrained subjects. After normalization with the foot length, it was found that the forefoot bones of the big and second toes were significantly longer in endurance runners than in untrained subjects (P<0.05 for both). Furthermore, longer forefoot bones of the big toe, but not of the second toe, correlated significantly with better personal best 5000-m race time in endurance runners (r=-0.322, P=0.031). The present findings demonstrated that forefoot bones were longer in endurance runners than in untrained subjects. These findings were similar to our findings for sprinters. In addition, we found that longer forefoot bones may be advantageous for achieving higher running performance in endurance runners.